Relativism about truth : a critique - Hamilton, Richard (Trinity College (Dublin, Ireland). Philosophy Department, 2012)
This thesis examines John MacFarlane's attempt to make sense of relative truth, but concludes by rejecting the coherence of such an attempt, on the grounds that it fails to adequately address a problem that was posed by Gareth Evans.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin.